Intra‐tumoral tumor infiltrating Lymphocyte‐T CD8+ and chemotherapy response in colorectal cancer: A prospective observational study - Budiman, Deny; Lukman, Kiki; Rudiman, Reno; Am Am Setya Sulthana, Bambang; Sribudiani, Yunia; Nugraha, Prapanca; Y. Hasibuan, Lisa; M. Dewayani, Birgitta (Trends in Immunotherapy, 2024)
Background: The immunotherapy approach to colorectal cancer is becoming one of the key approaches to colorectal cancer treatment. One of the components of immune responses is tumor‐infiltrating lymphocyte CD8+ cells (TILs CD8+). While chemotherapy is one of the main treatments for colorectal cancer, we need to consider immunotherapy for advanced colorectal cancer. Thus, this study is aimed at finding the association between TIL CD8+ expression and chemotherapy response. Methods: This is a prospective cohort study with colorectal cancer patients in the Digestive Surgery division of a tertiary general hospital in West Java, Indonesia. An immunohistochemistry examination was used to evaluate the expression of TIL CD8+. The response evaluation criteria in solid tumors (RECIST) were used for the evaluation of chemotherapy response. Results: There were 53 research subjects included. There were 20 (37.7%) subjects with high expression of TILs CD8+; there were 30 (56.6%) subjects in stage III, followed by stage IV (17.32%) and stage II (6.11%). There were 18 subjects (34%) who showed progressive disease, 17 subjects (32.1%) showed partial response, and 16 subjects (30.2%) with high expression of TILs CD8+ showed partial chemotherapy response. The TILs CD8+ expression showed no significant relationship with age, sex, subtype, grade, or tumor location, but showed a significant relationship with stage and chemotherapy response (P < 0.05). Conclusion: High TILs CD8+ expression show a relationship with better chemotherapy response and a better prognosis based on disease stage in colorectal cancer patients.